Espaços Escolares. Integração das (novas) necessidades infraestruturais - Anna Kazimirko (2020)
The present work is based on the study of different strategies for integrating (new) infrastructural needs into the Modernization Program for Secondary Education School. That its' temporal proximity to regulatory changes in the national legislative framework, it brings a multidisciplinary and multiscale response, making this Program one of the most important between architecture and new infrastructures. The historical legislative and infrastructural context of the school building is analyzed, as well as the influences what determine its' development, responsible tutelage, and the evolution of regulatory programs and standards. The school building is one of the first buildings in which the approach to health and hygiene issues calls for a concern that is reflected in the characterization of spaces and in the evolution of construction methods. Public health and the efficiency of systems that provide thermal comfort in spaces are themes of great importance for the creation of a physical-constructive environment that stimulates students and provides them with conditions for cognitive development. In a course that guides the development of school buildings in the regulatory and infrastructural scope, the knowledge is compiled for the analysis of five schools integrated in a public Program for the modernization of secondary schools. From the different approaches and methodologies that infrastructures acquire in the design process, we seek to understand what the consequences of the new infrastructures in space were, and to what extent their design was conditioned by the most recent regulatory directives.